A Quantum Entanglement Swapping Secret Sharing Agreement Model - Shuyue Wu (Institute of Advanced Engineering and Science, 2016)
A verifiable quantum secret sharing protocol model is proposed based on entanglement swapping. The dealer communicates with the participants one by one. The detection pattern or information pattern are choosed by uniform distribution, until he can make sure the information safe to the participant, and then he communicates with the next participant. This agreement not only is to avoid eavesdropping outside, and it can prevent internal fraud, thus the accuracy and security are ensured for information sharing, the verifiable results are achieved.